Long-term results of radio(chemo)therapy in metastatic carcinoma to cervical lymph nodes from an unknown primary. Adult Comorbidity Evaluation 27 score as a predictor of survival - Pala, Miloslav; Novakova, Pavla; Pechacova, Zdena; Vesela, Lucie; Vrana, Antonin; Sukova, Jarmila; Holeckova, Petra; Drbohlavova, Tereza; Podlesak, Tomas; Petruzelka, Lubos (Strahlentherapie und Onkologie, 2023)
PURPOSE: To evaluate the effectiveness and toxicity of curative (chemo)radiotherapy in patients with metastatic carcinoma to cervical lymph nodes from an unknown primary. METHODS: Retrospective study of 90 consecutive patients, treated with curative radiotherapy from 2003 to 2018 (median age 59 years; current/former smokers 76%) was conducted. The distribution of nodal staging was as follows: N1: 12%, N2a: 21%, N2b: 43%, N2c: 10%, N3: 13%. In 62% of patients, neck dissection was performed before radiotherapy. Concomitant chemotherapy was given to 64% of patients. RESULTS: The median follow-up of surviving patients was 86 months. The median total radiotherapy dose achieved was 70 Gy. The 5‐ and 10-year locoregional control were 84% in both cases, while 5‐ and 10-year distant control were 90% and 89%, respectively. A primary tumor in the head and neck area was detected in only 2 patients. No patient had an initial failure in the pharyngeal axis or contralateral cervical nodes. The 5‐ and 10-year overall survival were 55% and 42%, respectively. Severe early toxicity occurred in 71%; severe late toxicity in 33% of patients. Multivariate analysis demonstrated N‐status (hazard ratio [HR] 2.424; 95% confidence interval [CI] 1.121-5.241; p = 0.024) and comorbidity scores assessed by ACE-27 (Adult Comorbidity Evaluation; HR 3.058; 95% CI 1.489-6.281; p = 0.002) as two independent prognostic factors for overall survival. CONCLUSION: The results of our work study demonstrate the high effectiveness of curative (chemo)radiotherapy on the pharyngeal axis and bilateral cervical nodes with long-term locoregional and distant control in 3/4 of the treated patients. N‐status and comorbidity scores were shown as strong prognostic factors influencing overall survival.
Keywords: Retrospective Studies; Lymphatic Metastasis; retrospektivní studie; Humans; karcinom; Carcinoma; Neoplasm Staging; staging nádorů; lidé; Middle Aged; lidé středního věku; Neoplasms, Unknown Primary; Head and Neck Neoplasms; Lymph Nodes; nádory hlavy a krku; nádory neznámé primární lokalizace; dospělí; Adult; lymfatické metastázy; lymfatické uzliny